The role of institutional change in improving the quality of health services: An applied study At the Civil Hospital in Khamis Mushait - Alshahrani, Ayidh Hamoud; Alshehri, Abdullah Mohammed; Alqahtani, Saad Awad (Journal of Economic, Administrative and Legal Sciences, 2025)
Government hospitals face increasing challenges amid rapid developments in the healthcare field, necessitating fundamental changes in healthcare service delivery methods and quality improvement. The study problem focuses on determining the role of institutional change in improving healthcare service quality at the Civil Hospital in Khamis Mushait, where deficiencies were observed in organizational structure development, employee culture change programs, and modern technology adoption challenges. The study’s significance lies in providing an integrated framework linking institutional change with healthcare service quality, helping develop health policies, improve institutional performance, and enhance service efficiency. The study hypothesized a positive relationship between institutional change dimensions (technological, organizational, human, cultural) and healthcare service quality, and that employees’ perceptions are influenced by demographic variables. The study employed a descriptive analytical approach with a randomly selected sample of 188 employees. Results revealed a strong positive impact of institutional change on healthcare service quality, with the technological dimension showing superiority at a mean of 4.12, followed by the organizational dimension at 3.95. The study identified challenges related to change resistance and weak technological infrastructure. Recommendations included strengthening technological infrastructure, developing continuous training programs, improving organizational communication systems, adopting a change-supportive culture, establishing a specialized change management unit, and developing an integrated system for measuring and monitoring healthcare service quality.